"Someone Should Do Something": Replication and an Agenda for Collective Action. Issue 1 (2nd January 2016) - Kerr, Gayle; Schultz, Don E.; Lings, Ian
Abstract : This article provides insights into barriers to replication research and presents an agenda identifying "who" should do "what" to robustly advance knowledge in disciplines of advertising and marketing. A Delphi study, showing consensus of opinion among international experts in the replication process—authors, editors, and reviewers—is presented. The study engages the problem from a triadic perspective and highlights differences in thinking among these stakeholder groups. In presenting an agenda for collective action, the article seeks to stimulate debate regarding the merits of undertaking and publishing replication research in enhancing the credibility of the theoretical foundations of our disciplines.